Stakeholder workshop insights: Research progress in the beans and maize value chains of Honduras and future research opportunities - Colindres, Mirian; Reyes, Byron A. (2023)
The Rethinking Food Markets Initiative organized a workshop in Honduras for the basic grains sector. The goal was to discuss research progress on inclusive growth and sustainable innovation in the food processing of maize and beans. The workshop shared the progress of a scoping study, a pilot study, and the baseline survey, and prioritized future research efforts.